Comment on "Thermal effects – an alternative mechanism for plasmon-assisted photocatalysis" by Y. Dubi, I. W. Un and Y. Sivan, Chem. Sci., 2020, 11, 5017. Issue 33 (13th August 2020) - Jain, Prashant K.
Abstract : A range of chemical reactions occurring on the surfaces of metal nanoparticles exhibit enhanced rates under plasmonic excitation. It is not straightforward to distinguish between photochemical and photothermal effect using Arrhenius fitting of the reaction rates alone.